2018
DOI: 10.1016/j.aop.2018.01.011
|View full text |Cite
|
Sign up to set email alerts
|

The Quantum Cheshire Cat effect: Theoretical basis and observational implications

Abstract: The Quantum Cheshire Cat (QCC) is an effect introduced recently within the Weak Measurements framework. The main feature of the QCC effect is that a property of a quantum particle appears to be spatially separated from its position. The status of this effect has however remained unclear, as claims of experimental observation of the QCC have been disputed by strong criticism of the experimental as well as the theoretical aspects of the effect. In this paper we clarify in what precise sense the QCC can be regard… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…(16) was first obtained in [20], where the complex valued fraction in brackets was called "the weak value (WV) of the opera-torQ 2 ". Written in this way, a WV looks like a physical variable of a new kind [21], whose physical significance is still discussed in the literature (see, for example [22], [23]). However the first expression in the r.h.s.…”
Section: H Hertzmentioning
confidence: 99%
“…(16) was first obtained in [20], where the complex valued fraction in brackets was called "the weak value (WV) of the opera-torQ 2 ". Written in this way, a WV looks like a physical variable of a new kind [21], whose physical significance is still discussed in the literature (see, for example [22], [23]). However the first expression in the r.h.s.…”
Section: H Hertzmentioning
confidence: 99%
“…In the discussion of the Hardy's paradox [12]-[15] the particle is suspected of simultaneously "being and not being" at the same location [13]. The so called "quantum Cheshire cat" scheme [17]- [21] promises "disembodiment of physical properties from the object they belong to".…”
Section: Pacs Numbersmentioning
confidence: 99%
“…We can also check our calculation by evaluating P(γ) directly. Upon passing a beamsplitter each wave packet is reduced by a factor of 1/ Our last example involves the so called "quantum Cheshire cat" model [17], [18] still discussed in the literature [21]. The authors of [21] suggested that "most of the works criticizing the effect did not introduce a proper framework in order to analyze the issue of spatial separation of a quantum particle from one of its properties", so we take another look at the problem.…”
Section: Composite Systems the Hardy's "Paradox"mentioning
confidence: 99%
See 1 more Smart Citation
“…Quantum Chesire Cat has opened up new understanding of quantum systems and attracted a lot of debates and discussions [3,7,8,14]. It pertains not only to photons and their polarizations but can, in principle, be observed with any quantum system and its property, such as neutron and its magnetic moment, electron and its charge and so on.…”
Section: Introductionmentioning
confidence: 99%